End-of-Life Care During the Pandemic. Perspectives from Healthcare Professionals in Home-based Palliative Care in Colombia - León Delgado, Marta Ximena; Acero, Angela; Buitrago Reyes, Lina Angélica; Rodríguez Campos, Luisa Fernanda; Pino Pinzón, Carmen Juliana; Consuegra Pareja, César; Cuenca Anacona, Linda Lorena; González Salazar, Laura Vanessa; Michelsen Andrade, Mariana (Iatreia, 2024)
Introduction: The COVID-19 pandemic has had a significant social and health impact. Given the high risk of contagion and the potential collapse of the healthcare system, strategies such as social isolation, the use of personal protective equipment, and an increased reliance on telemedicine were adopted. These measures altered the dynamics of end-of-life patient care. Methodology: This observational cross-sectional study explored the experiences of home care staff providing end-of-life care and the impact of the pandemic on the care process, as well as on their quality of life and emotional well-being. A survey incorporating the adapted Care Of the Dying Evaluation (iCODE) questionnaire was conducted, alongside an assessment of quality of life using question 30 of the EORTC QLQ, and emotional wellbeing using the PANAS scale. Results: The experiences of 131 deceased patients were characterized. Professionals reported adequate therapeutic efforts in managing pain, dyspnea, and delirium. Additionally, they noted that the pandemic impeded treatment in 24% of the patients. The average quality of life score for professionals was 6 points, with a predominantly positive affect reported. Conclusions: Healthcare professionals in home-based care programs observed that the pandemic affected the treatment of nearly a quarter of end-of-life patients. Nonetheless, they highlighted that satisfactory symptomatic care and control were maintained. Additionally, they reported an adequate quality of life.